Redesign and Fabrication of a Folding Ergonomic Laptop Desk for College Students - Mojtaba Jafarvand; Saeid Ahmadi; Ali Safari Variani; sakineh varmazyar (Shiraz University of Medical Sciences, 2022)
Background: Awkward posture during work is one of the most critical risk factors for musculoskeletal disorders. A laptop desk fitting with users' body dimensions plays a crucial role in maintaining proper posture and reducing musculoskeletal disorders. This study aimed to redesign and fabricate a folding ergonomic laptop desk for college students.Methods: In this experimental applied study, two hundred and seven college students were considered participants to design an ergonomic laptop desk and fifty students for posture evaluation. Six anthropometric dimensions were measured: height, the height of elbows in the sitting position, elbow-elbow breadth, the length and height of both knees in the cross-legged sitting posture, and the length of the elbow-fingers. Then, two best selling laptop desks were selected and the RULA method assessed laptop users' posture. Finally, using students' anthropometric dimensions (n=207), a new laptop desk was designed and built in 2017.Results: The height of our designed laptop desk is adjustable (range of 20-28 cm), with a variable inclination of the desk (0- 34 degrees). It is possible to shorten or lengthen desk legs (48-72 cm), and a special plate of the mouse (19×46 cm) supports both elbows on the sides of the desk. RULA method showed action level 3, which required early change in desks 1 and 2.Conclusion: Applying user›s and expert opinions, measuring users› body dimensions, and applying those dimensions in design and construction can play a significant role in improving and correcting the laptop›s desks so that it could result in suitable posture in students.